Premature ovarian failure could be an alarming sign of polyglandular autoimmune dysfunction - Saif Aasem (Sciendo, 2017)
A 31-year-old lady, diagnosed to have premature ovarian failure in the gynecology clinic, was referred for endocrine assessment because of an abnormal thyroid function test. Clinical examination revealed hypotension, and fungal skin infection under her atrophic breasts. Thyroid stimulating hormone (TSH) level was very high. Assessment of the suprarenal function revealed evidence of Addison’s disease. Polyglandular autoimmune dysfunction was diagnosed. She was treated with prednisone, fludrocortisone, and levothyroxine with significant improvement of her general condition and blood pressure.